Effects of Different Molasses Levels and Slow-Release Urea Combinations on Growth Performance, Serum Biochemistry, Rumen Fermentation, and Microflora of Holstein Fattening Bulls - Zhiyuan Xu; Shuaihong Li; Fangzhou Yu; Yinghao Huang; Tao Xie; Hanbing Bian; Longfei Lv; Yapeng Hu; Ruoran Tao; Caiyun Fan; Sijia Liu; Jianbo Cheng (Agriculture)
The aim of this study was to investigate the effects of different combinations of molasses levels and slow-release urea on Holstein fattening bulls. Sixty Holstein fattening bulls of a similar age, weight, and health status were randomly divided into four groups of fifteen Holstein fattening bulls each. All of the treatments were as follows: (1) basic diet group (CON); (2) 2% molasses slow-release urea group (LMU); (3) 4% molasses slow-release urea group (MMU); and (4) 6% molasses slow-release urea group (HMU). The results of the study showed that the MMU had an outstanding performance, with a 13.3% increase in average daily weight gain compared with the control group, a significant decrease in feed conversion ratio (p < 0.05), and a significant increase in apparent digestibility of crude protein (p < 0.05). In terms of serum biochemical indices, blood ammonia and alanine aminotransferase (ALT) concentrations were significantly higher in the MMU than in the CON (p < 0.05). The rumen pH of all treatment groups was lower than that of the CON (p < 0.05), whereas the concentrations of microbial crude protein (MCP), as well as acetic acid, propionic acid, and total volatile fatty acids (TVFA) were significantly higher in both the MMU and HMU (p < 0.05). The dominant phyla in each group were Bacteroidetes, Firmicutes, and Patescibacteria, and the relative abundance of Bacteroidetes in the MMU increased by 5.47% compared with that in the CON. In the MMU, Prevotellaceae, Lachnospiraceae, and Ruminococcaceae increased by 9.03%, 0.67%, and 3.43%, respectively, compared with the CON. The economic benefit analysis showed that the daily feeding cost of fattened cattle in the MMU was reduced by RMB 1.62 yuan, and the daily farming benefit of each cow was increased by RMB 7.19 yuan. In conclusion, the MMU was effective in improving the growth performance of fattening cows, optimizing rumen fermentation, reducing cost, and increasing profit, which is a nutritional strategy with great application value.